Infectiousness of TB patients and factors associated with the airborne survival of Mycobacterium tuberculosis: Tuberculosis Infectiousness and TrANsmission (TITAN) study - Mahlobo, Zama (Stellenbosch : Stellenbosch University, 2024)
Thesis (PhD)--Stellenbosch University, 2024.